Компаративна евалуација на солзен менискус со предно-сегментна оптичка кохерентна томографија и квантитативен тест Ширмер 2 - Дума, Христиан (Медицински факултет, УКИМ, Скопје, 2019)
Introduction: With the development of modern ophthalmology, timely and proper diagnosis of the ocular surface is of great importance. In addition to medical importance, diagnostics is also important for improving the quality of social life of the patient. Тear meniscus is related to the amount of tear secretion and stability, therefore the tear meniscus is good indicator of the total amount of tears. Recognizing the importance of tear secretion in maintaining the normal physiology of the anterior surface of the eye and providing good quality of vision, modern anterior segment optical coherence tomography (OCT) takes a special place for proper and timely diagnosis and classification of dry eye. Purpose: The aim of this study was to make a comparative evaluation and correlation of the tear meniscus parameters obtained by anterior segment optical coherent tomography with an already well established and proven Schirmer 2 test for basal tear secretion, as well as comparison of data obtained from qualitative methods (Tear breakup time and Lid-paraller conjunctival folds’ test.) Material and methods: In this retrospective- prospective cross section study, were included 300 patients by random choice. The follow up period of the patients was one year in UC for eye diseases in anterior segment department. The patients were divided according to the age in four groups, according to gender and by data obtained by Schirmer test in four groups (I group with results ≥15mm, II group 10-15mm, III group 5-10mm, and IV group <5mm). All patients underwent tear meniscus measurement by anterior segment optical coherence tomography (Topcon SL SCAN-1 and Topcon biomicroscopeslit lamp DV-3), basal tear secretion through Schirmer 2 test (with Whatman No.41 filter paper 5mm x 33mm), TBUT and LIPCOF test by biomicroscope Topcon Slit Lamp DV-3. Results: The lowest tear secretion (<5mm) measured by Shirmer 2 test was found among female patients (22,4 %) compared to males (4%). According to age, lowest values were found in the oldest group of 60-79 years (21,6% right eye and 19,2 left eye). The analysis of parameters from tear meniscus with anterior OCT, showed that gender had no significant influence on the height, depth and area of tear meniscus of the both eyes. Age and tear meniscus parameters correlated indirectly. The smallest height of tear meniscus was found in patients in the oldest group 60-79 y (approximately 177.4±59.1 right eye and 184.08±52.1 left eye). Comparison between Schirmer 2 test and anterior OCT showed positive, direct correlation. The patients with basal secretion ≥15mm had the highest tear meniscus, (mean 269.01±138.6 right eye and 303.53 ± 172.8 left eye), and the patients with basal secretion <5mm had the lowest tear meniscus, (mean 142.63 ± 48.1 right eye and 154.19 ± 53.1 left eye). The depth of tear meniscus was the shallowest (106.08 ± 39.1 right eye and 99.31 ± 33.6 left eye) in the patients with basal secretion <5mm, and deepest (230.12 ± 170.5 right eye and 228.31 ± 143.7 left eye) at the respondents with basal secretion ≥15mm. Area of tear meniscus was the smallest (7858.02± 4853.6 right eye and 8073.39 ± 5294.6 left eye) in the patients with basal secretion <5mm, and biggest (37691.74 ± 59397.1 right eye and 41545.26 ± 54949.3 left eye) in the patients with basal secretion ≥15mm. The patients with basal secretion ≥15 mm had gradus 0 LIPCOF, (90.9% right eye and 89.4 left eye), while gradus 3 LIPCOF was found at the patients with basal secretion <5mm (42.9% right eye and 28.26% left eye). The patients with result of TBUT test ≥15sec. had basal secretion ≥15mm (99% right eye,97.6% left eye), while the patients with TBUT <5 sec, had basal secretion <5mm, (71.4% right eye and 21.74% left eye). Conclusion: Optical coherence tomography is non-invasive method and technique that is expected to have good results in evaluation of tear meniscus and diagnosis of dry eye syndrome. Through anterior segment OCT we can precisely measure the height, depth and surface of the tear meniscus. Those parameters correlate well with Schirmer, TBUT and LIPCOF test, that helps us in diagnosing dry eye syndrome.
Докторска дисертација одбранета во 2019 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Билјана Јанеска.
Keywords: tear meniscus, anterior segment optical coherence tomography, Schirmer, TBUT, LIPCOF